The relationship between mean platelet volume and metabolic syndrome in patients with type 2 diabetes mellitus: A retrospective study. Issue 13 (2nd April 2021) - Ding, Qinpei; Wang, Fangwei; Guo, Xintong; Liang, Min
Abstract : Abstract: This study aimed to investigate the association between mean platelet volume (MPV) and metabolic syndrome (MetS) in patients with type 2 diabetes mellitus (T2DM). Data for 1240 patients with T2DM admitted to the Department of Endocrinology at the First Affiliated Hospital of Guangxi Medical University between January 1, 2017 and June 1, 2020 were collected retrospectively via electronic medical records, including demographic information, complete blood count, lipid profile, and glucose metabolism indexes. MetS was defined according to the Chinese Diabetes Society. Among the 1240 patients enrolled, 873 (70.40%) had MetS. MPV was significantly higher in patients with MetS ( P  < .001). For individual MetS components, MPV was significantly higher in the presence of abdominal obesity ( P  = .013) and hypertriglyceridemia ( P  = .026), but did not differ in the presence of elevated blood pressure ( P  = .330) or low high-density lipoprotein cholesterol ( P  = .790). Moreover, MPV was independently associated with MetS after adjustment for sex, smoking, alcohol drinking, white blood cell count, fasting C-peptide, and body mass index (odds ratio 1.174, 95% confidence interval 1.059–1.302). The odds ratio for MetS in the highest tertile, compared with the lowest MPV tertile, was 1.724 (95% confidence interval 1.199–2.479, P for trend = .003) after multiple adjustment. In stratified analyses, the positive correlation of MPV with MetS was significant only in patients who were older, male, or overweight, or who had poor glycemic control. In conclusion, high MPV was positively associated with the presence of MetS in patients with T2DM, particularly older, male, or overweight patients, or those with poor glycemic control.